A Process Evaluation of a Substance Use Brief Intervention for Adolescents in a Psychiatric Inpatient Program. (June 2020) - Johnson, Sarah E; Lapomardo, Andrea; Thibeau, Heather M; Altemus, Melanie; Hunt, Jeffrey I; Wolff, Jennifer C
The present study represents a two-phase process evaluation of the implementation of Screening, Brief Intervention, and Referral to Treatment (SBIRT) on an adolescent psychiatric inpatient unit. The first phase analyzed uptake efforts using chart review data, which revealed that 158 (16.8%) of 942 hospitalized patients ( Mean age = 15.81, SD  = 1.24) were eligible to receive the brief intervention; however, only 30 (19%) adolescents received the intervention, 15 (9.5%) declined treatment, and 113 (71.5%) were never offered. The second phase involved directed content analyses of clinical staff and providers' perceived facilitators and barriers to the implementation. Qualitative findings revealed that providers and staff accepted and agreed with the use of the brief substance use intervention, though perceived time constraints, competing demands, and insufficient staffing interfered with implementation across disciplines. Barriers included patients' length of stay and competing treatment priorities. Several recommendations emerged including, utilization of non-clinical staff, a clear administration protocol, and the use of computer-based interventions. Findings from the present study shed light on the need to consider alternate or more streamlined substance use treatments such as computerized approaches and focus on ways in which protocol can be modified to fit the needs within an acute, short-term setting.